Car Ownership and Status: Implications for Fuel Efficiency Policies from the Viewpoint of Theories of Happiness and Welfare Economics - Verhoef, Erik T.; van Wee, Bert (European Journal of Transport and Infrastructure Research, 2000)
Research on ‘happiness’ suggests that once an average per capita income of around US$ 10,000 is achieved in a country, further increases in income will not lead to a significant increase in happiness. Additional income will probably often be spent on the satisfaction of mainly ‘relative’ needs, of which ‘status goods’ would be one example. From that perspective, an overall shift to more fuel-efficient cars (i.e. smaller cars with less power) would not necessarily, or only to a limited extent, result in less happiness. From a welfare economic perspective, the satisfaction of the relative needs pertaining to consumption can be considered as a form of consumption externalities. This creates a welfare economic basis for government intervention. A model in which these consumption externalities are studied is presented here. Government intervention would include stimulating consumption of lowerstatus goods and discouraging consumption of higher-status ones. We speculate, however, that to achieve a significant increase in the fuel efficiency of a country’s car fleet through pricing policies, huge price increases may often be needed. As acceptance of price increases as a policy instrument is often low, ‘fee-bates’ and tradeable permits may be more preferable instruments.